Energy potential of the 1002 area; and the Arctic Coastal Plain Domestic Energy Security Act of 2000 : hearing before the Committee on Energy and Natural Resources, United States Senate, One Hundred Sixth Congress, second session on . S. 2214 . April 5, 2000. - United States. Congress. Senate. Committee on Energy and Natural Resources. (Washington : U.S. G.P.O. : For sale by the U.S. G.P.O., Supt. of Docs., Congressional Sales Office, 2000)
Shipping list no.: 2001-0017-P. Includes bibliographical references. Mode of access: Internet.